PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN REMAJA PEREMPUAN DESA JIPURAPAH TENTANG ANEMIA DAN GIZI SEIMBANG : The Effect of Education on Adolescent Girls' Knowledge Level Jipurapah Village About Anemia and Balanced Nutrition - Nurul Hidayah; Agustin Nur Imaningsih; Ella Damayanti Damayanti; Nova Wilujeng Fitria; Mu’tiyah Putri Ramadhani; Wahyu Ellen Merisdiansyah; Gabiela Rahmadhani Vasthia Shahla (LPPM STIKES Pemkab Jombang, 2022)
ABSTRACT Introduction : The prevalence of anemia in Indonesia aged 15-24 years is 18.4%. In women, most cases of anemia are caused by iron deficiency anemia. Adolescent girls have a high risk of anemia, especially iron deficiency anemia because adolescent girls go through the menstrual cycle and adolescence requires higher nutrition for growth and development. Education about anemia and balanced nutrition is needed to increase adolescent knowledge. This study aims to determine the effect of education on the level of knowledge of adolescent girls in Jipurapah village about anemia and balanced nutrition. Method : This research design uses pre-experimental analytic with one group pre post test design to analyze the knowledge level of adolescent girls before and after the educational intervention. The population is female adolescent in Jipurapah village. The sample is a teenage girl in Jipurapah village who attends the MERETAS ASA Women's School (Anaemia and Stress Free Teenage Media). The sampling technique used purposive sampling.Data analysis used t test (paired t-test). Results : Most of the respondents are in the age range of 16-18 years (43%), most of them have junior high school (43%) and high school (43%). The level of knowledge of adolescent girls about anemia and balanced nutrition in the pre test obtained 52% level of sufficient knowledge and 48% level of good knowledge, while the post test obtained 9.5% level of sufficient knowledge and 90.5% level of good knowledge. There is a difference between education and knowledge level with a significance value of 0.001. There is a difference in the level of knowledge before and after education with a significance value of 0.000, which means that there is a significant effect of educational intervention on the level of knowledge of adolescent girls about anemia and balanced nutrition. Conclusions : There is a significant effect of educational intervention on the level of knowledge of adolescent girls about anemia and balanced nutrition in Jipurapah Village, Plandaan District, Jombang Regency.